Collaborative Governance in Natural Disaster Mitigation Management in The Pangandaran Beach - Kurnia Illahi Manvi; Fahmi Muhammad (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2022)
Pangandaran is the 16th district out of 514 districts/cities in Indonesia with a high potential for disasters. In its management, there are still different views regarding disaster mitigation by stakeholders, namely the Government, Private, and Community sectors. This study aims to look at the existing conditions of disaster mitigation carried out in Pangandaran and collaborative governance in disaster mitigation management at Pangandaran Beach. This study uses a qualitative approach by determining the participants from primary stakeholders interested in tourism and natural disasters. Structural and non-structural disaster mitigation has been carried out in Pangandaran using the tsunami risk management master plan manual (BNPB 2012). There are 11 indicators that 2 indicators are still lacking, namely related to disaster evacuation orientation maps and early warning system tools which are very crucial when a disaster occurs. The result of Collaborative governance adopted by the theory of DeSeve (2007) is still not done optimally because tourism management and disaster mitigation have not been integrated and are still running from each party, namely the government, the private sector and public funds, of the 8 indicators only part of the commitment to a common purpose which began to form because they realized that the seriousness of the disaster issue that in Pangandaran can have an impact on all parties.